Spatial Filter Housing for Enhancement of the Shielding Effectiveness of Perforated Enclosures with Lossy Internal Coating: Broadband Characterization - Khalid F. A. Hussein (International Journal of Antennas and Propagation)
This work is concerned with studying and enhancement of the electromagnetic shielding effectiveness of open metallic enclosures with openings over a wide range of the frequency including the UHF band. The suggested methods depend on the suppression of the excessive power penetrating the enclosure cavity especially at its resonances by a variety of methods that include increasing aspect ratio of the rectangular aperture, splitting the opening into a number of apertures, coating the internal walls of the metallic enclosure with a multilayered lossy material of the appropriate conductivity profile, and, finally, placing the metallic enclosure inside a spatial filter housing. A minimum value of 20 dB is achieved for the shielding effectiveness using the suggested methods. The present work also provides a study to investigate the effect of the direction and polarization of the incident plane wave on the shielding effectiveness of the enclosure.